Effect of Temperature on the Physiological Response of Enhalus acoroides Seedlings - Nugraha, Aditya Hikmat; Anggraini, Rika; Desrica, Ramona; Hidayati, Jelita Rahma; Addini, Indri; Halim, Muhamad (Marine Science Department Diponegoro University, 2023)
Increasing sea surface temperatures as an effect of global warming can affect the survival of marine organism, among these marine organisms is seagrass. Temperature is one factor that can determine seagrass's physiological response in maintaining its life, including in the early stages of life in seagrass seedlings. This research aims to study the effect of temperature on the physiological response of Enhalus acoroides seedlings such as growth rate, leaf tissue anatomy, and chlorophyll content. The method used was an experiment in the laboratory. The seagrass seedlings were grown in an aquarium with three sea water temperature treatments (28°C, 31°C and 35°C) for 8 weeks of maintenance. The choice of sea water temperature treatment of 28°C (A) as a control is the optimal temperature range for seagrass, the treatment temperature of 31°C (B) refers to previous study, i.e. the temperature in the area of origin of the seagrass meadow, and the treatment temperature of 35°C (C) is considered as an estimate of temperature under the scenario of. The growth rate and the average leaf length were more optimal with a high chlorophyll content found at a temperature treatment of 28°C. The highest anatomical size of leaf tissue in the upper and lower epidermis was observed at 31°C, while the most extensive mesophyll tissue was observed at 35°C. In this study, temperature significantly affected the growth rate, average leaf length, anatomical structure of mesophyll tissue, and chlorophyll content of the Enhalus acoroides seedlings.